Agricultural production systems modelling and software: Current status and future prospects. (October 2015) - Holzworth, Dean P.; Snow, Val; Janssen, Sander; Athanasiadis, Ioannis N.; Donatelli, Marcello; Hoogenboom, Gerrit; White, Jeffrey W.; Thorburn, Peter
Abstract: During the past decade, the application of agricultural production systems modelling has rapidly expanded while there has been less emphasis on model improvement. Cropping systems modelling has become agricultural modelling, incorporating new capabilities enabling analyses in the domains of greenhouse gas emissions, soil carbon changes, ecosystem services, environmental performance, food security, pests and disease losses, livestock and pasture production, and climate change mitigation and adaptation. New science has been added to the models to support this broadening application domain, and new consortia of modellers have been formed that span the multiple disciplines. There has not, however, been a significant and sustained focus on software platforms to increase efficiency in agricultural production systems research in the interaction between the software industry and the agricultural modelling community. This paper describes the changing agricultural modelling landscape since 2002, largely from a software perspective, and makes a case for a focussed effort on the software implementations of the major models. Highlights: The agricultural modelling community has broadened its scientific focus over the last decade. The software implementations of the leading agricultural models hasn't changed significantly in the last decade. A focussed effort on agricultural modelling software and process is needed.